Cosmic ray radio detection with the IceCube Surface Array Enhancement - Venugopal, Megha; IceCube Collaboration (2023)
The IceCube Neutrino Observatory has been recording neutrino events and cosmic rays at the South Pole for more than a decade. The cosmic ray observatory of this experiment, IceTop with 162 Cherenkov tanks, has played an important part in understanding the high-energy universe. A Surface Array Enhancement(SAE), made up of scintillators and radio antennas, is planned to address the rising uncertainties from IceTop measurements due to snow accumulation and to improve measurement capabilities. A prototype station was deployed in January 2020 and has taken measurements which have been correlated with reconstructed events from IceTop. This contribution focuses on the current status of radio detection of cosmic rays at the SAE. The calibration and characterization of hardware components were performed and prepared for deployment. Reconstruction of Xmax, the atmospheric depth of the shower maximum, was done with initial measurements and with data from IceTop. The main goal is to characterize uncertainties and to prepare the experiment to do physics.